(untitled) (Journal of Hama University, 2024)
This research aimed to study the variations in the characteristics of efficient investment portfolios resulting from the use of both the Resampled Efficiency Technique and (mean-variance) model, by applying it to a sample of shares of companies listed on the Damascus Stock Exchange during the period (2/20/ (2019-15/6/2023) To achieve this goal, two curves were designed for efficient investment portfolios, after measuring the expected returns from the stocks nominated for conservative investment, in addition to measuring the degree of risk associated, based on the closing prices of the stocks published on the website of the Damascus Stock Exchange. By comparing the characteristics of efficient portfolios resulting from the application of both the technique and the model, the differences in the characteristics of efficient investment portfolios resulting from using each of them in the process of selecting investment portfolio components become clear. The research reached a set of results, the most prominent of which was the difference in the characteristics of the investment portfolios resulting from the application of the (mean-variance) model, from the characteristics of the investment portfolios resulting from Resampled Efficiency Technique, in terms of the degree of diversification of the component portfolios, the graphical representation of the efficient frontier, and the returns. Expected portfolios and accompanying degrees of risk.